The impact of the Nkangala region mine closure on the former mine employees and their dependents - Mathe, Siphiwe Lorraine Thato (University of the Free State, 2023)
The mine closure represents a turning point in the lives of former miners and those who are dependent on them, having a significant impact on their socioeconomic well-being. In the context of South Africa's Mpumalanga in the Nkangala Region, this study explored the complex effects of mine closure on ex mine workers and their dependents. The study demonstrated that mine closure contributed to psychological discomfort, loss of benefits like housing, medical aid, and life insurance, dysfunctional families, as well as other related social problems, because it also impacted the livelihood of former miners and their dependents negatively. The study suggests social entrepreneurship as a form of intervention that will address the social ills and economic impacts, along with training in transferable skills for industries other than mining.
Dissertation(MDS (Development Studies))--University of the Free State, 2023
Keywords: Mine closure; Ex-mine works; Impact; Coal mining